Drug-induced Fanconi syndrome in patients with kidney allograft transplantation - Tang, Zhouqi; Li, Tengfang; Dai, Helong; Feng, Chen; Xie, Xubiao; Peng, Fenghua; Lan, Gongbin; Yu, Shaojie; Wang, Yu; Fang, Chunhua; Nie, Manhua; Yuan, Xiaoqiong; et al. (Frontiers in Immunology, 2022)
Background: Patients after kidney transplantation need to take long-term immunosuppressive and other drugs. Some of these drug side effects are easily confused with the symptoms of Fanconi syndrome, resulting in misdiagnosis and missed diagnosis, and causing serious consequences to patients. Therefore, improving awareness, early diagnosis and treatment of Fanconi syndrome after kidney transplantation is critical. Methods: This retrospective study analyzed 1728 cases of allogeneic kidney transplant patients admitted to the Second Xiangya Hospital of Central South University from July 2016 to January 2021. Two patients with Fanconi syndrome secondary to drugs, adefovir dipivoxil (ADV) and tacrolimus, were screened. We summarized the diagnostic process, clinical data, and prognosis. Results: The onset of Fanconi syndrome secondary to ADV after renal transplantation was insidious, and the condition developed after long-term medication (>10 years). It mainly manifested as bone pain, osteomalacia, and scoliosis in the late stage and was accompanied by obvious proximal renal tubular damage (severe hypophosphatemia, hypokalemia, hypocalcemia, hypouricemia, glycosuria, protein urine, acidosis, etc.) and renal function damage (increased creatinine and azotemia). The pathological findings included mitochondrial swelling and deformity in renal tubular epithelial cells. The above symptoms and signs were relieved after drug withdrawal, but the scoliosis was difficult to rectify. Fanconi syndrome secondary to tacrolimus has a single manifestation, increased creatinine, which can be easily confused with tacrolimus nephrotoxicity. However, it is often ineffective in dose reduction of tacrolimus, and proximal renal failure can be found in the later stage of disease development. There was no abnormality in the bone metabolism index and imageological examination findings. The creatinine level decreased rapidly, the proximal renal tubule function was normal, and no severe electrolyte imbalance or urinary component loss occurred when the immunosuppression was changed from tacrolimus to cyclosporine A. Conclusions: For the first time, drug-induced Fanconi syndrome after kidney transplantation was reported. These results confirmed that the use of ADV and tacrolimus after kidney transplantation can have serious consequences, some of which are irreversible. Greater understanding of Fanconi syndrome after kidney transplantation is necessary in order to avoid incorrect and missed diagnosis.